Penatalaksanaan Fisioterapi Pada Kasus Cervical Root Syndrome Di Rs Pku Muhammadiyah Surakarta - Prananda Septiyana, Achmad, Sugiono S.Fis,.MH.Kes (2015)
Background: Cervical Root Root Cervical Syndrome Syndrome is a condition caused by irritation or cervical nerve root compression by disc protrusion invertebralis, the symptoms are neck pain that spreads to the shoulders, upper arms or forearms, parasthesia, and weakness or muscle spasm, if complaints very severe surgery can be done to improve the condition of patients. Objective: To determine the management of transcutaneous electrical nerve stimulation (TENS), Infrared (IR) can reduce pain in conditions Root Cervical Syndrome and to determine the management of Exercise therapy can increase the area of motion in the neck in a state of Root Cervical Syndrome. Results: Reduction of silent pain of T1 = 2 to T6 = 0 then tenderness of T1 = 5 to T6 = 2 and painful motion becomes T6 T1 = 7 = 2, Improved LGS flexi T1 = 6cm into T6 = 10cm, extension T1 = 6 became T6 = 12, lateral right flexi T1 = 8,5cm be T6 = 12cm, left lateral flexi T1 = 8,5cm be T6 = 12cm, right rotation becomes T6 T1 = 10cm = 12cm, left rotation becomes T6 T1 = 10cm = 12cm. Methods: a case study in which patients studied and observed its development as a whole and routine Conclusion: Various problems that arise on condition of cervical root of this syndrome are pain and limited LGS (range of motion). Physiotherapy modalities used to solve the problem that TENS, IR and Exercise Therapy. In addition patients be educated to do the exercises at home as it has been taught by the therapist. With the implementation modalities of therapy using the results obtained show a positive development which is evidenced by the decrease in pain (Pain Silence, Press and painful motion) and Enhanced LGS (range of motion).